Prospective evaluation of clinical outcomes in all-comer high-risk patients with aortic valve stenosis undergoing medical treatment, transcatheter or surgical aortic valve implantation following heart team assessment - Dubois, Christophe (Oxford University Press, 2013)
OBJECTIVES: Transcatheter aortic valve implantation (TAVI) has been proposed as a treatment alternative for patients with aortic valve stenosis (AS) at high or prohibitive risk for surgical aortic valve replacement (AVR). We aimed to assess real-world outcomes after treatment according to the decisions of the multidisciplinary heart team. METHODS: At a tertiary centre, all high-risk patients referred between 1 March 2008 and 31 October 2011 for symptomatic AS were screened and planned to undergo AVR, TAVI or medical treatment. We report clinical outcomes as defined by the Valve Academic Research Consortium. RESULTS: Of 163 high-risk patients, those selected for AVR had lower logistic EuroSCORE and STS scores when compared with TAVI or medical treatment (median [interquartile range] 18 [12–26]; 26 [17–36]; 21 [14–32]% (P = 0.015) and 6.5 [5.1–10.7]; 7.6 [5.8–10.5]; 7.6 [6.1–15.7]% (P = 0.056)). All-cause mortalities at 1 year in 35, 73 and 55 patients effectively undergoing AVR, TAVI and medical treatment were 20, 21 and 38%, respectively (P = 0.051). Cardiovascular death and major stroke occurred in 9, 8 and 33% (P < 0.001) and 6, 4 and 2% (P = 0.62), respectively. For patients undergoing valve implantation, device success was 91 and 92% for AVR and TAVI, respectively. The combined safety endpoint at 30 days was in favour of TAVI (29%) vs AVR (63%) (P = 0.001). In contrast, the combined efficacy endpoint at 1 year tended to be more favourable for AVR (10 vs 24% for TAVI, P = 0.12). CONCLUSIONS: Patients who are less suitable for AVR can be treated safely and effectively with TAVI with similar outcomes when compared with patients with a lower-risk profile undergoing AVR. Patients with TAVI or AVR have better survival than those undergoing medical treatment only.